The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.54203/scil.2021.wvj30
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Chicken Anaemia Virus Circulating in Commercial Poultry Flocks in Egypt during 2020

Abstract: Chicken Anemia Virus (CAV) is an extremely contagious immunosuppressive disease causing high economic losses in poultry production. In the present study, tissue samples (bone marrow, thymus, and spleen) were collected from 86 different broiler chicken farms located in fourteen governorates in Egypt during 2020. They suffered from retard growth, weakness, and a drop in egg production with an observed mortality rate ranged 5-15%. A total of 26 samples were positive for CAV using PCR in six governorates in Lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…DNA extraction from the examined tissue homogenates was performed utilizing the QIAamp DNA extraction kit (Qiagen, Germany, Cat. No 51304), Quality of extracted DNA was measured by Nabi Nanodrop spectrophotometer |(MicroDigital Co., Ltd., Korea) and DNA concentrations of positive samples were listed in ( Supplementary Table 1 ) to amplify a 675 bp DNA fragment of the Vp1 gene ( 21 ), the oligonucleotide primers 5’-GAC TGT AAG ATG GCA AGA CGA GCT C-3′ and 5’-GGC TGA AGG ATC CCT CAT TC-3′ were employed, spanning nucleotides from 823 to 1498, numbering is corresponding to the Del-Rose strain (GenBank AF313470) ( 3 ). The PCR assay was conducted using the Emerald Amp®GT PCR master mix (Cat No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA extraction from the examined tissue homogenates was performed utilizing the QIAamp DNA extraction kit (Qiagen, Germany, Cat. No 51304), Quality of extracted DNA was measured by Nabi Nanodrop spectrophotometer |(MicroDigital Co., Ltd., Korea) and DNA concentrations of positive samples were listed in ( Supplementary Table 1 ) to amplify a 675 bp DNA fragment of the Vp1 gene ( 21 ), the oligonucleotide primers 5’-GAC TGT AAG ATG GCA AGA CGA GCT C-3′ and 5’-GGC TGA AGG ATC CCT CAT TC-3′ were employed, spanning nucleotides from 823 to 1498, numbering is corresponding to the Del-Rose strain (GenBank AF313470) ( 3 ). The PCR assay was conducted using the Emerald Amp®GT PCR master mix (Cat No.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, numerous studies have reported the circulation of CAV in chicken farms among Egypt. Therefore many studies was done to molecular detect and characterize of CAV as a trail to control of CAV ( 3 ).…”
Section: Introductionmentioning
confidence: 99%